Personalized goal setting and predictors of functional gains following constraint-induced movement therapy in preschool-aged children with unilateral cerebral palsy - Youngsub Hwang; Jeong-Yi Kwon (PLoS ONE, 2025)
Objective This study aimed to identify caregiver-selected goal characteristics that predict functional improvements following constraint-induced movement therapy (CIMT), offering novel insights into personalized rehabilitation for younger children with unilateral cerebral palsy (UCP). Methods This study included 19 children with UCP aged 4–6 years who participated in a three-week CIMT program comprising 15 sessions (30 hours total), during which the unaffected hand was constrained to encourage intensive use of the affected limb. Caregivers identified five meaningful rehabilitation goals per child using the Canadian Occupational Performance Measure, categorizing them into self-care, productivity, or leisure domains and ranking them by importance. Upper-limb function was objectively evaluated using the Assisting Hand Assessment before and immediately after CIMT. Linear regression analyses identified the factors influencing goal selection, and least absolute shrinkage and selection operator regression determined whether prioritized goal types predicted improvements in upper limb function. Results Self-care goals were most frequently selected (72.6%), followed by leisure (26.3%) and rarely productivity (1.1%). Leisure goal selection was significantly associated with greater baseline upper limb range of motion and lower baseline occupational performance scores. The higher prioritization of goals involving quiet leisure activities (e.g., arts, crafts, computer play) and dressing tasks (e.g., buttoning, zipping) significantly predicted greater functional improvements post-intervention. Conclusion This study provides important new evidence indicating that caregiver-selected rehabilitation goals that are closely aligned with a child’s latent motor capacities positively affect functional outcomes. These findings underscore the clinical importance of individualized, family-driven goal setting for optimizing therapeutic effectiveness in preschool-aged children with UCP.